A Formula for the kth Derivative of e-z 2F2(a,r+1;b+1,r;z) - Rathie, A. K.; López-Bonilla, J.; Sánchez-Meléndez, Gabriela (Journal of the Institute of Engineering, 2016)
Available with full text. Journal of the Institute of Engineering, 2015, 11(1): 88-90